Protective role of N-acetylcysteine (NAC) on human sperm exposed to etoposide - Baetas, J (2019)
Background: Although recent progress in cancer treatment has increased patient survival and improved quality of life, reproductive side effects are still for concern. One way to decrease gonadal impairment is to use cytoprotectors. In testicular cancer, etoposide is generally used in combination with other agents, but there are no in-vitro studies of sperm exposure to etoposide and cytoprotectors, namely N-acetylcysteine (NAC). Methods: Twenty semen samples were individually divided into five groups: control, incubation with NAC alone, incubation with etoposide alone, sequential exposure of NAC followed by etoposide (pre-treatment) and sequential exposure of etoposide followed by NAC (post-treatment). Sperm characteristics, chromatin condensation (aniline blue), DNA fragmentation (TUNEL), oxidative stress (OxyDNA labelling) and glutathione quantification were used to evaluate the capabilities of NAC as a prophylactic (pre-treatment) or ameliorator (post-treatment) agent over the effects caused in sperm during in-vitro exposure to etoposide. Results: No deleterious effects were observed on sperm motility or sperm membrane integrity. Results revealed that prophylactic use of NAC (pre-treatment) increased rates of immature sperm chromatin as compared to ameliorator use of NAC (post-treatment), and increased rates of sperm DNA fragmentation in relation to controls. Pre and post-treatment with NAC increased oxidative levels in comparison to controls, but also increased levels of cellular antioxidant glutathione. Conclusions: The results indicate that NAC has the ability to counteract etoposide-induced toxicity rather than preventing the etoposide cytotoxic effects over sperm DNA, suggesting that the administration of NAC to cells formerly exposed to etoposide is preferable to its prophylactic use. As the results evidenced that NAC seems to be more efficient in attenuating sperm etoposide cytotoxic effects instead of being used as a chemoprophylactic agent, this reinforces the idea that there might be a new NAC mechanism over DNA.